Generalized plotting tool development for post silicon component validation - Neves Filho, Nilson de Aguiar [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
This thesis explores the development and implementation of a web-based plotting tool for data visualization in Post Silicon Validation (PS Val) processes at Infineon Technologies. PS Val is critical for understanding the post-production behavior of microprocessors and microcontrollers, ensuring their optimal performance. The research addresses the need for an automated, efficient, and standardized plotting environment to replace time-consuming manual processes, which are often platform-dependent and lack comprehensive tools. The study employs the Model-View-Controller (MVC) architecture to develop ValiBridge, a dynamic, scalable, and user-friendly web application utilizing HTML, CSS, and JavaScript powered by Bootstrap 4 and Plotly.js libraries. The research involved a thorough literature review, field surveys, and iterative development cycles. Initial results indicate that the ValiBridge platform successfully integrates data preprocessing, transformation, and visualization, providing a broad tool focused on user experience and efficiency. While the current implementation fulfills 50% of its potential in terms of tools and features, it establishes a robust foundation for future enhancements and wider industry application.

Esta tese explora o desenvolvimento e a implementação de uma ferramenta de plotagem baseada na web para visualização de dados nos processos de Validação Pós-Silício (PS Val) na Infineon Technologies. A PS Val é crítica para compreender o comportamento pós-produção de microprocessadores e microcontroladores, garantindo seu desempenho ideal. A pesquisa aborda a necessidade de um ambiente de plotagem automatizado, eficiente e padronizado para substituir processos manuais que consomem muito tempo, frequentemente dependentes de plataformas e que carecem de ferramentas abrangentes. O estudo emprega a arquitetura \textit{Model-View-Controller} (MVC) para desenvolver o ValiBridge, uma aplicação web dinâmica, escalável e amigável ao usuário que utiliza HTML, CSS e JavaScript auxiliado pelas bibliotecas Bootstrap 4 e Plotly.js libraries. A pesquisa envolveu uma revisão bibliográfica detalhada, pesquisa de campo e ciclos de desenvolvimento iterativos. Os resultados iniciais indicam que a plataforma ValiBridge integra com sucesso o pré-processamento, a transformação e a visualização de dados, proporcionando uma ferramenta completa focada na experiência do usuário e na eficiência. Embora a implementação atual atenda a 50% das ferramentas e recursos em potencial, ela estabelece uma base sólida para futuras melhorias e uma aplicação mais ampla na indústria.
Desenvolvimento de ferramenta para plotagem generalizada visando validação de componentes pós-silício
Keywords: Web site development Software; Charts, diagrams, etc; Validation Studies; Sites da Web Desenvolvimento Software; Cartas, diagramas, etc; Estudos de validação